Patterns of reinnervation and motor unit recruitment in human hand muscles after complete ulnar and median nerve section and resuture. Issue 3 (March 1987) - Thomas, C K; Stein, R B; Gordon, T; Lee, R G; Elleker, M G
Abstract : Following complete ulnar or above-elbow median nerve sections, there was no significant correlation between motor unit size (twitch amplitude) and recruitment threshold, as assessed by spike triggered averaging. This absence of orderly recruitment was attributed to misdirection of motor axons during regeneration. Following median nerve section at wrist level, where the reinnervated muscles have more synergistic actions, orderly recruitment by size appeared to be re-established. Thus, the size principle of motor unit recruitment can be re-established after nerve section in humans, if motor axons innervate their original muscles or ones with closely synergistic functions.